PENGGUNAAN MODEL PROBLEM BASED INSTRUCTION DENGAN MEDIA KARTU PINTAR UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 47 KOTA JAMBI - Syuryani Syuryani. (Jurnal Pesona Dasar, 2019)
Science subjects need to be given to all students starting from elementary school to equipstudents with the ability to develop knowledge and understanding of science concepts that areuseful and applicable in everyday life. Application of the Problem Based Instruction model islearning that involves the presentation of authentic and meaningful situations and serves as abasis for investigation and investigation for students. The formulation of the problem in thisstudy is: Is the Problem Based Instruction model with smart card media able to improvescience learning outcomes in third grade students of SD 47 / IV Jambi? From the results ofdata analysis, it was found that student learning achievement experienced an increase fromcycle I to cycle III, namely, cycle I (67.65%), cycle II (76.62%), and cycle III (87.50%). Theconclusion of this study is that Problem Based Instruction learning methods with Smart Cardmedia can have a positive effect on learning motivation of Students of Jambi ElementarySchool 47 / IV Class III of Semester I 2018/2019 academic year and this learning model canbe used as an alternative teaching field of study Natural Sciences.